Comparison of retinal nerve fibre layer thickness measurements calculated by the optic nerve head map (NHM4) and RNFL3.45 modes of spectral-domain optical coherence tomography (RTVue-100). Issue 6 (27th May 2010) - Shin, Chul Jin; Sung, Kyung Rim; Um, Tae Woong; Kim, Yoon Jeon; Kang, Sung Yong; Cho, Jung Woo; Park, Seong Bae; Park, Joo Ri; Kook, Michael S
Abstract : Aim: To evaluate and compare retinal nerve fibre layer (RNFL) thickness measured by direct scanning (RNFL3.45 mode) and re-sampling from datasets (NHM4 mode) of RTVue-100 optical coherence tomography (OCT). Methods: Thirty-six healthy subjects and 76 subjects with glaucoma were imaged with Stratus OCT (fast RNFL mode, RNFL3) and RTVue-100 OCT (NHM4 (RNFL1) and RNFL3.45 (RNFL2) modes). Measurement reproducibility was assessed in NHM4 and RNFL3.45 modes of RTVue-100 OCT (intraclass correlation coefficient (ICC)). Agreement between different RNFL measurements was analysed by Bland–Altman plot. The areas under the receiver operating characteristic (ROC) curves (AUCs) for discrimination between healthy and glaucoma were compared between the different RNFL measurements. Results: Both NHM4 and RNFL3.45 modes showed excellent measurement reproducibilities (ICC 0.831–0.978). RNFL thicknesses by two different modes of the RTVue-100 OCT, and by the Stratus OCT, were correlated in all sectors, including average. There was no significant difference between RNFL1 and RNFL2 data. However, RNFL thickness in glaucomatous eyes by the RTVue-100 OCT was significantly greater than that measured by Stratus OCT. RNFL thicknesses determined by the two different modes of RTVue-100 OCT were in excellent agreement (95% limits of agreement −6.53 to 6.95 μm). All three RNFL measurements showed good glaucoma discrimination ability (AUC = RNFL1 0.970, RNFL2 0.962, RNFL3 0.971). Conclusions: RNFL thickness determined by direct scanning and re-sampling from datasets of RTVue-100 OCT were in good agreement. However, both measurements in glaucomatous subjects were significantly different from those with the Stratus OCT. Those findings should be considered when a patient is followed-up using different types of OCT.